Tailoring the Switching Dynamics in Yttrium Oxide‐Based RRAM Devices by Oxygen Engineering: From Digital to Multi‐Level Quantization toward Analog Switching. (9th September 2020) - Petzold, Stefan; Piros, Eszter; Eilhardt, Robert; Zintler, Alexander; Vogel, Tobias; Kaiser, Nico; Radetinac, Aldin; Komissinskiy, Philipp; Jalaguier, Eric; Nolot, Emmanuel; Charpin‐Nicolle, Christelle; Wenger, Christian; et al.
Abstract: This work investigates the transition from digital to gradual or analog resistive switching in yttrium oxide‐based resistive random‐access memory devices. It is shown that this transition is determined by the amount of oxygen in the functional layer. A homogeneous reduction of the oxygen content not only reduces the electroforming voltage, allowing for forming‐free devices, but also decreases the voltage operation window of switching, thereby reducing intra‐device variability. The most important effect as the dielectric becomes substoichiometric by oxygen engineering is that more intermediate (quantized) conduction states are accessible. A key factor for this reproducibly controllable behavior is the reduced local heat dissipation in the filament region due to the increased thermal conductivity of the oxygen depleted layer. The improved accessibility of quantized resistance states results in a semi‐gradual switching both for the set and reset processes, as strongly desired for multi‐bit storage and for an accurate definition of the synaptic weights in neuromorphic systems. A theoretical model based on the physics of mesoscopic structures describing current transport through a nano‐constriction including asymmetric potential drops at the electrodes and non‐linear conductance quantization is provided. The results contribute to a deeper understanding on how to tailor materials properties for novel memristive functionalities. Abstract : Digital‐to‐gradual transition of the switching dynamics is achieved in yttria‐based resistive random‐access memory via oxygen engineering of the functional layer. A homogeneous reduction of the oxygen content results in lowering forming and operation voltages, and in an increased accessibility of quantized conduction states. A physics‐based generalized quantum point contact model is proposed to explain the observed nonlinear conductance quantization.